2012
DOI: 10.1039/c1dt11804h
|View full text |Cite
|
Sign up to set email alerts
|

Pyochelin, a siderophore of Pseudomonas aeruginosa: Physicochemical characterization of the iron(iii), copper(ii) and zinc(ii) complexes

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen, synthesizing two major siderophores, pyoverdine (Pvd) and pyochelin (Pch), to cover its needs in iron(III). If the high affinity and specificity of Pvd toward iron(III) (pFe = 27.0) was well described in the literature, the physicochemical and coordination properties of Pch toward biologically relevant metals (Fe(III), Cu(II) or Zn(II)) have been only scarcely investigated. We report a thorough physico-chemical investigation of Pch (potentiometry, spectropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
167
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(171 citation statements)
references
References 142 publications
3
167
0
1
Order By: Relevance
“…As reported in previous studies, Fe(III) addition caused notable shifts in the UV-visible absorption spectra of Ybt and pyochelin, consistent with the formation of Fe(III) complexes (19,46,47). The escherichelin UV-visible absorption spectrum was similarly shifted following exposure to equimolar Fe(III) ( Figure 3D).…”
Section: Escherichelin Binds Fe(iii)supporting
confidence: 68%
“…As reported in previous studies, Fe(III) addition caused notable shifts in the UV-visible absorption spectra of Ybt and pyochelin, consistent with the formation of Fe(III) complexes (19,46,47). The escherichelin UV-visible absorption spectrum was similarly shifted following exposure to equimolar Fe(III) ( Figure 3D).…”
Section: Escherichelin Binds Fe(iii)supporting
confidence: 68%
“…5 and 6). This is an intriguing result considering the significantly lower affinity for iron of pyochelin than that of pyoverdine, at least in vitro (9,10,12,13). Since it has been demonstrated that pyoverdine has a primary role in withdrawing iron from transferrin and lactoferrin (61,62) and is essential for P. aeruginosa growth in human serum (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…First of all, P. aeruginosa produces two siderophores, pyoverdine and pyochelin, endowed with very different structural and functional properties, and both are capable of chelating ferric ions (Fe 3ϩ ). Pyoverdine is a peptidic siderophore containing two hydroxamic groups and a fluorescent dihydroxyquinoline chromophore, which create a very efficient iron coordination center (9)(10)(11), while pyochelin is a salicylate-based siderophore with a lower affinity for iron (12,13). Both siderophores are actively translocated across the outer membrane upon binding to specific receptors, namely, the FptA and FpvA outer membrane proteins for pyochelin and pyoverdine transport, respectively (14).…”
mentioning
confidence: 99%
“…In addition, increasing numbers of lower-denticity siderophores are being isolated from bacterial cultures and found to coordinate Fe(III) and mediate its uptake (14)(15)(16)(17)(18). For example, the trilactone backbone of enterobactin makes it prone to hydrolysis, and although this lability is necessary to allow the intracellular release of Fe(III) from the siderophore, it in addition leads to its slow degradation in aqueous media (7,(19)(20)(21).…”
mentioning
confidence: 99%